ANALISIS PERKEMBANGAN PENDUDUK TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI INDONESIA - Andini Ayuningtyas; Fitrah Sari Islami (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The demographic structure and change that happens through time is one of the most influential factors on economic development. Ignoring the demographic structure might result in discrepancies, which will affect planning issues. Ultimately, this results in inequalities in several economic, social, and political spheres. Meanwhile, the economic sector is one of the most effective areas of the demographic structure. This research aims to determine the extent to which population development factors impact Indonesia's work force participation rate. This research employs a time-series analysis technique using the ARDL Error Correction Model analytical instrument. ARDL models may be used to models with varying degrees of stationarity. Short-term fertility characteristics had a significant and negative influence on the work force participation rate, according to the findings of the investigation. On the other side, the dependence ratio and short-term government expenditures have a significant and positive influence on the work force participation rate. However, global factors have insignificant influence on the labor force participation rate in long-term.